Management of multilingualism and indigene teaching for an intercultural bilingual education in Argentina (Práxis Educativa, 2013)
Current paper presents the first outcome of an ongoing sociolinguistic research on bilingual intercultural education (EIB) in Argentina. The aim of this study is to identify some elements for an account of the role of language in the social process that involves native people by highlighting the manner in which language usage participate in the struggle for material resources and how social representations and linguistic ideologies are involved in the unequal distribution of resources among indigene groups and in the maintenance of social inequalities. The case of a population that called El Algarrobo has been analyzed. Native young people are trained as teachers and gradually incorporated in schools of the region. In such a process the educational institutions define the roles for native teachers and the place of languages. Results show that the management of languages is linked to the process of social struggle where languages have a key role. The conception of bilingualism, the assessments of native teachers with a competence of Spanish and classroom language practices evidence the distance between meanings in official discourses on EIB in Argentina and the meaning EIB has in day-to-day practice in the classroom and in the school. Keywords: Intercultural Bilingual Education. Sociolinguistics. Multilingualism.